2011
DOI: 10.3109/01480545.2011.589446
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of selenium on gentamicin-induced oxidative stress and nephrotoxicity in rats

Abstract: Gentamicin (GM) is a widely used antibiotic against serious, life-threatening infections, but its usefulness is limited by the development of nephrotoxicity. The present study was designed to determine the protective effect of selenium (Se) in GM-induced nephrotoxicity in rats. Experiments were done on 32 adult Wistar rats divided into four groups of 8 animals each. The GM group received gentamicin (100 mg/kg), whereas the GM+Se group received the same dose of GM and selenium (1 mg/kg) by intraperitoneal (i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
4
34
0
3
Order By: Relevance
“…Also, a highly significant decrease SOD and catalase activity was reported in this study, these observations are in agreement with those of, Yaman and Balikci [23] . Reduced glutathione act as an intracellular free radical scavengers and protect cells against radical mediated lipid peroxidation [26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a highly significant decrease SOD and catalase activity was reported in this study, these observations are in agreement with those of, Yaman and Balikci [23] . Reduced glutathione act as an intracellular free radical scavengers and protect cells against radical mediated lipid peroxidation [26] .…”
Section: Discussionmentioning
confidence: 99%
“…(Randjelovic et al, 2012) limits its therapeutic usefulness. Garlic has been shown to possess profound antioxidants properties (Lawal et al, 2011) and its use in this study to ameliorate the hepatotoxic and oxidative effects of gentamycin is instructive.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Thus, in mice, this drug significantly increases kidney myeloperoxidase activity, lipid peroxidation, and protein carbonylation. It has been shown that the resulting acute renal failure is caused by ROS, and the use of M40403, which is a low-molecular-weight mimetic of superoxide dismutase, attenuates this damage (64,65,75). Similarly, proteomic analysis implicates Gmmediated oxidative stress in Leishmania since the proteins affected by drug exposure included the thiol-redox control system (76).…”
Section: Figmentioning
confidence: 99%
“…We interpret this to show that, at higher concentrations, the ability of Gm to disrupt protein synthesis is strong enough not to be affected by the defective antioxidant defense of the mutant, but at a low concentration, the drug relies also on the added effect of oxidative stress to be effective. A strong enough attack on elements of the E. coli antioxidant defense, for example, by small-molecule inhibitors of the proteins identified above, should therefore enhance Gm effectiveness in combating this disease and permit the use of lower drug concentrations, thereby minimizing drug side effects such as nephrotoxicity (64,65).…”
Section: Fig 4 Deletion Of Ros Quencher Proteins or Ppp Enzymes Rendementioning
confidence: 99%
“…proximal tubular cells as the possible mechanism through which gingerol and other antioxidant substances ameliorate GM-induced nephrotoxicity. Other substances with antioxidant properties have been tested in aminoglycoside-induced nephrotoxicity (42)(43)(44). In the present study, we used a model that approximates clinical practice: an in vivo study, protective substance administration initiated after the use of the toxic agent, and evaluation of functional parameters with clinical relevance (e.g., CL CR ), in addition to histopathology, inflammatory gene expression, and oxidative status.…”
Section: Figmentioning
confidence: 99%